The Battle of France, 1940 - Goutard, Colonel A.; Translated by Captain A.R.P. Burgess (Rawalpindi Army Education Press, 1986)
Reassessment of the fall of France in 1940. Over-all campaign plans of Germany are compared with those of France and her allies, and each battle is analyzed for its part in the fall.
Include Bibliography and Index
Keywords: The Battle of France, 1940 -- World War (1939-1945) -- Military campaigns -- Western Front (World War (1939-1945)